Customization in Standard Hierarchy Report for Improving Activity Based Costing Process - Taufiq Maulana Firdaus; Muhardi Saputra; Tien Fabrianti Kusumasari (International Journal of Innovation in Enterprise System, 2022)
Activity based costing process is a process to accurately manage the cost allocation process for a product. With the development of technology, the activity-based costing process has been integrated with the ERP system so that it can relate to all business processes as a whole and can reduce expenses to manage the flow of information systems within the company. It is necessary to determine a fast business process for the allocation of these costs so that a product can be produced. A standard hierarchy is needed which serves as the center of the business process for determining the activity-based costing process. This process is still done manually so that it slows down the business determination process in the activity-based costing process. This research will implement the search function in the ABC system by creating a reporting system that can search business processes in the standard hierarchy in SAP S/4HANA. This research will use SEEM embed with SDLC method where this method pays attention from the perspective of the user and the company to produce an efficient ABC process with the company's objectives.